Impacts of teachers' competency on job performance in research universities with industry characteristics: Taking academic atmosphere as moderator - Anguo Xu; Long Ye (Journal of Industrial Engineering and Management (JIEM), 2014)
Purpose: Research universities with industry characteristics play an irreplaceable role in national economic development and social development. With the rapid development of research universities with industry characteristics in China, these universities face new challenges in managing teachers and promoting their quality. This paper aims to examine the impact of teachers' competency on job performance in research university with industry characteristics. Design/methodology/approach: Based on the behavioral event interview and questionnaire methods, a four-dimension (i.e. basic quality, teaching ability, industry awareness and research capacity) competency model was proposed, the influence mechanism of competency on job performance was examined using empirical research. Findings: We found that there is a significant positive correlation between the teachers' competency level, four dimensions and job performance in research universities with industry characteristics, especially between research capacity, teaching ability, industry awareness and job performance. And academic atmosphere plays a regulatory role in the interaction between the competency and job performance. Practical implications: Our findings can help to improve the management level of teachers in research universities with industry characteristics. Originality/value: The paper introduces the competency theory to the teacher management in research universities with industry characteristics, and gives some interesting findings.
Keywords: 650; industry characteristics; research universities; competency; job performance; academic atmosphere